KEAMANAN PANGAN KOMODITAS TRANSGENIK: STUDI KASUS SEDIAAN PAKAN HIJAUAN DARI DAUN TEBU OVEREKSPRESI SoSPS1 - A Bagus Nur Sudrajat; Nurhayati Nurhayati; Bambang Sugiharto (Agroindustrial Technology, University of Trunojoyo Madura, 2021)
Sugarcane (Saccharum officinarum L) is a sucrose-producing plantation that has been cultivated in various countries. Genetically modified sugar cane sugar cane plants are sugar cane plants that are assembled biotechnology through overexpression of the SoSPS1 gene. The SoSPS1 gene is responsible for the biosynthesis of sucrose sugar in leaves. Waste in the form of leaves, shoots, and bagasse has not been used optimally as animal feed. Thus it takes a lot of innovation and appropriate technology in the use of sugarcane waste for animal feed, so that it is expected to achieve zero waste farming systems that can be utilized all without being wasted and polluting the environment. As an alternative feed for livestock, then genetically engineered sugar cane must be tested for feed safety. Feed safety testing includes substantial equivalence value and feed digestibility test in which genetically engineered products have nutritional and digestive values commensurate with conventional products. Substantial value of sugarcane planted by genetically engineered overexpression of SoSPS1 gene did not differ significantly compared to conventional sugarcane. However, there are some significant nutritional content, but these values are still in the range of values in the OECD.